Cognitive profiles of healthy siblings of first‐episode schizophrenia patients. Issue 3 (2nd June 2020) - Voráčková, Veronika; Knytl, Pavel; Španiel, Filip; Šustová, Petra; Renka, Jiří; Mohr, Pavel
Abstract: Aim: Cognitive deficit in psychotic illness is intensively studied, different cognitive subtypes have been suggested. In recent years, there has been an increase in the number of studies in patients with schizophrenia and their relatives searching for endophenotypes of the disease. The aim of our study was to investigate cognitive performance and cognitive subtypes in the siblings of the patients. Methods: Four groups of subjects were included: patients with a first episode of psychotic illness, the siblings of these patients, and two control groups. All the study subjects (N = 84) had a battery of neuropsychological tests that measured basic cognitive domains – memory, executive functions, attention, visual‐spatial skills, language skills and psychomotor speed – administered to them. The data were assessed with pairwise t‐tests for group comparisons. The siblings were distributed into three groups according to their cognitive performance: non‐deficit, partial deficit, and global deficit. Subsequently, the patients were assigned into three groups corresponding to their siblings' performance. Results: Our results revealed attenuation of abstract thinking in the siblings compared to the controls. As expected, the patients showed impairment across all cognitive domains. The patients and siblings demonstrated similar profiles in each subtype, in the severity of their impairment, and in their patterns of cognitive performance. Conclusions: Our results suggest that the cognitive profile can be considered as an endophenotype of psychotic disorders.